PENGARUH MODAL USAHA DAN TENAGA KERJA TERHADAP PENDAPATAN UMKM DI KOTA BANJARMASIN (STUDI KASUS USAHA MIKRO) - Nadia Nadia; Penta Lestarini Budiati; Rizki Amalia Afriana (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2026)
The purpose of this study was to determine the effect of business capital and labor partially or simultaneously on the income of MSMEs in Banjarmasin City. The study population was 31,231 MSMEs in Banjarmasin City in 2025, with a sample of 100 micro businesses. The research method is a quantitative descriptive regression model. The results of the study show that business capital and labor significantly affect the income of MSMEs in Banjarmasin City. Partially, business capital is proven to have an effect with a calculated t of 4.668> t table 1.984 and a significance of 0.000 <0.050, and labor with a calculated t of 3.429> t table 1.984 and a significance of 0.001 <0.050. Simultaneously, business capital and labor together have an effect with a calculated F value of 31.813> F table 3.09 and a significance of 0.000 <0.050. The conclusion of the study is that business capital and labor partially and simultaneously affect the income of MSMEs in Banjarmasin City.